Returning to foster care: Age and other risk factors. (September 2020) - Wulczyn, Fred; Parolini, Arno; Schmits, Florie; Magruder, Joseph; Webster, Daniel
Highlights: This is a multi-state study of foster care reentry following reunification and guardianship. We find that infants and teens face the highest risk of reentry. We also find a significant developmental effect: the risk of reentry rises with the onset of adolescene. Abstract: This study uses longitudinal administrative data from twenty U.S. states to examine the risk of returning to foster care after children are either reunified with their parents or placed with guardians outside the foster care system. Our sample for this analysis includes all children who, before age 18, exited their first spell to either reunification or placement with guardians between 2003 and 2010 with follow-up through December 31, 2017 (N = 607, 289). Focusing on demographics of the children, placement history and elapsed time since their exit from care as risk factors, a discrete time hazard model was specified to integrate children's development as a factor predictive of reentry. Subgroup analyses identified which children are most at risk of returning to care. Of all children who exited their first spell to reunification, 27% reentered care by 2018 and of all children who exited their first spell of foster care to live with a guardian, 17% reentered care by 2018. The study found older teens, children who experienced changes in care type before reunification, children who were discharged to reunification within six months of entering care, and children whose last placement was congregate care all show significant risks of reentry into care. Additionally, while the number of infants who enter, leave and return to care before their first birthday is relatively small, the children in this group have a substantial risk of re-entering care. State and local child welfare agencies can use the results of this study to target their service investments such as those they might support with federal Family First Prevention funds.